Preparation of non-porous microspheres with high entrapment efficiency of proteins by a (water-in-oil)-in-oil emulsion technique - Badri Viswanathan N.; Thomas P.A.; Pandit J.K.; Kulkarni M.G.; Mashelkar R.A. (My University, 2025)
Emulsification-solvent removal methods have been widely used for encapsulating bioactive macromolecules like proteins and polypeptides in biodegradable polymers. We report, a (water-in-oil)-in-oil emulsion technique wherein proteins and polypeptides differing in molecular weight and shape were encapsulated in polymers of current biomedical interest. When an oil was used as the processing medium in combination with a carefully selected mixed solvent system such that a stable (w/o1/o2 emulsion is formed and solvents are removed by a combination of extraction and evaporation, the entrapment efficiency was high and the product nonporous. The entrapment efficiency of globular proteins exceeded 90% while that of fibrous proteins was around 70%. Fracture studies revealed that the polymer matrix was dense. The mechanism of entrapment involved solvent-induced precipitation of the protein as the microspheres were being formed. The principle of the method will find use in preparation of non-porous polymer microparticles with reduced burst effect. Copyright (C) 1999 Elsevier Science B.V.